Functions of circular RNAs and their potential applications in gastric cancer. (1st February 2020) - Ruan, Yao; Li, Zhe; Shen, Yijing; Li, Tianwen; Zhang, Haiyan; Guo, Junming
ABSTRACT: Introduction : In recent years, circular RNAs (circRNAs) have emerged in the field of RNA research and their biological functions are now being gradually identified. circRNAs are divided into three categories: exonic circular RNAs (ecircRNAs), exon-intron circular RNAs (EIciRNAs), and intronic circular RNAs (ciRNAs). The circular structure of circRNAs confers unique biological characteristics upon them, such as enhanced stability over linear RNAs. Areas covered : circRNAs function to competitively bind with microRNAs (miRNAs) and proteins, participate in protein coding, regulate transcription, and form pseudogenes after reverse transcription. In gastric cancer, the circRNA-miRNA-mRNA axis is the most studied mechanisms underlying gastric cancer occurrence and development. Some specific and sensitive circRNAs, such as hsa_circ_102958, hsa_circ_0000520, and hsa_circ_0001017 may have potential diagnostic potential in early-stage gastric cancer. Abnormal expression of some circRNAs, including circ-LMTK2, circ-PSMC3, and circ-DLST are associated with the development of gastric cancer. Other circRNAs, such as hsa_circ_0001368, circ-ZFR, and circ-ERBB2, may also play important roles in gastric cancer treatment. Expert opinion : Exploring the roles of circRNAs in gastric cancer occurrence and development will help us to elucidate the functions of circRNAs and develop potential tools for early diagnosis and effective treatment of gastric cancer.